2023
DOI: 10.1002/chem.202203384
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Activation in the Gas Phase: Spectroscopic Characterization of C−N Coupling in the V3C++N2Reaction

Abstract: We report on cluster‐mediated C−N bond formation in the gas phase using N2 as a nitrogen source. The V3C++N2 reaction is studied by a combination of ion‐trap mass spectrometry with infrared photodissociation (IRPD) spectroscopy and complemented by electronic structure calculations. The proposed reaction mechanism is spectroscopically validated by identifying the structures of the reactant and product ions. V3C+ exhibits a pyramidal structure of C1‐symmetry. N2 activation is initiated by adsorption in an end‐on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In this regard, the study of gas-phase reactions under isolated conditions with well-characterized chemical and molecular structures constitutes an alternative way to probe the intrinsic structure–reactivity relationship of N 2 activation by metal clusters. With continuous efforts from many research groups, to date, a variety of homo/heteronuclear metal clusters have been successfully identified to be capable of fully cleaving the NN triple bond, the metal centers of which include Ti 2 , Gd 2 , Ta 2 , , Ta 3 , Ta 4 , Ta 6 , FeTa, V 3 , , FeV 2 , Sc 2 , Nb, ,, etc., as summarized in Figure . Considering the high NN bond strength, the mechanistic focus of these studies was often to elucidate the NN cleavage pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the study of gas-phase reactions under isolated conditions with well-characterized chemical and molecular structures constitutes an alternative way to probe the intrinsic structure–reactivity relationship of N 2 activation by metal clusters. With continuous efforts from many research groups, to date, a variety of homo/heteronuclear metal clusters have been successfully identified to be capable of fully cleaving the NN triple bond, the metal centers of which include Ti 2 , Gd 2 , Ta 2 , , Ta 3 , Ta 4 , Ta 6 , FeTa, V 3 , , FeV 2 , Sc 2 , Nb, ,, etc., as summarized in Figure . Considering the high NN bond strength, the mechanistic focus of these studies was often to elucidate the NN cleavage pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, N 2 is inert, and it owes its inertness to a strong and nonpolar triple bond, which possesses very low proton- and electron-affinities. Transition metal (TM) complexes are widely used to reduce N 2 . Nevertheless, the toxicity and high cost of many TMs have motivated scientists to seek environmentally friendly alternatives. One such alternative rests on the development of versatile main group complexes that can replace TM-based chemistry , and activate N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase reactivity studies of isolated clusters provide a unique approach to probe the reaction intermediates and understand the molecular-level details of elementary steps involved in the catalytic reactions. The reactions of bare metal clusters including homonuclear and heteronuclear metal clusters with N 2 have been extensively investigated to disclose the size effect in N 2 adsorption. Recently, the ligand effect of dopants like carbon, sulfur, hydrogen, and boron atoms in metal-based clusters has been emphasized. For example, it is revealed that hydrogen ligands could regulate the energy level of active orbital of metal clusters to promote nitrogen adsorption; an appropriate number of sulfur ligands can reduce the valence s-electron occupancy of the metal to enhance the reactivity of clusters toward N 2 ; carbon ligands are able to assist in the dissociation of N 2 molecules; boron ligands could participate in the cleavage of NN bond directly .…”
mentioning
confidence: 99%